2022
DOI: 10.1016/j.meegid.2022.105207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of miR-200c-3p and miR-421-5p levels during immune responses in the admitted and recovered COVID-19 subjects

Abstract: Angiotensin-converting enzyme 2 (ACE2) acts as a key receptor for the spike of SARS-CoV-2. Two main microRNAs (miRs), miR-200c-3p and miR-421-5p, are considered to modulate the expression of ACE2 gene and alterations in the expression of these miRNAs may influence the outcomes of COVID-19 infection. Accordingly, we examined whether miRNAs directing ACE2 expression altered in the SARS-CoV-2 infection. 30 patients with COVID-19 included in the study. At the time of admission and discharge, the expression of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Indeed, hyperglycemia is the principal cause of induced oxidative stress; therefore, exposing ECs to high glucose led not only to oxidative stress but also to upregulation in miR-200c, which subsequently induced EC apoptosis and senescence via Notch1 inhibition [ 42 , 43 ]. Since hyperglycemia augments miR-200c expression in target cells (EC), but not in the immune regulatory cells such as PBMCs, a possible explanation is that miR-200c expression may be downregulated indirectly by factors such as proinflammatory cytokines; as detected by previous studies, IL-6 is negatively correlated with miR-200c-3p expression in inflammatory diseases [ 44 , 45 ] and also IL-8 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hyperglycemia is the principal cause of induced oxidative stress; therefore, exposing ECs to high glucose led not only to oxidative stress but also to upregulation in miR-200c, which subsequently induced EC apoptosis and senescence via Notch1 inhibition [ 42 , 43 ]. Since hyperglycemia augments miR-200c expression in target cells (EC), but not in the immune regulatory cells such as PBMCs, a possible explanation is that miR-200c expression may be downregulated indirectly by factors such as proinflammatory cytokines; as detected by previous studies, IL-6 is negatively correlated with miR-200c-3p expression in inflammatory diseases [ 44 , 45 ] and also IL-8 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…77 Of note, hsa-miR-200c-3p was found downregulated in the blood of COVID-19 patients in an independent study. 53 Molinero et al studied miRNA expression in bronchial aspirate specimens of COVID-19 and non COVID-19 ICU patients. Rather than comparing the expression of single miRNAs, they compared expression ratios and found several differences of the expression of certain miRNA ratios when COVID-19 and non-COVID-19 as well as ICU survivors and nonsurvivors were compared (Table 2).…”
Section: Mirnas In Respiratory Specimensmentioning
confidence: 99%
“…ACE2 acts as a key receptor for the spike of SARS-CoV-2, and it is crucial for the virus entry into the cells. MR-200c-3p and miR-421-5p can target ACE2, and their expression was decreased in the blood of SARS-CoV-2 patients at hospital admission, also suggesting a relation with the degree of infection [ 39 ]. On the other hand, Papannarao observed an increased expression of miR-200c in the blood of obese patients and suggested that increased angiotensin II, followed by inhibition of ACE2 through miR-200c targeting, may increase the severity of the SARS-CoV-2 infection in obese people [ 51 ].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Several miRNAs are described as key factors in SARS-CoV-2 human infection, regulating the inflammation, interfering with the innate immune response and assuming antiviral roles [ 2 , 37 ]. Further, some miRNAs were reported as crucial for virus entrance in the host cells that were involved in ACE2 levels regulation [ 38 , 39 ]. Furthermore, there are diverse studies demonstrating that miRNAs inhibit SARS-CoV-2 replication and inhibit spike expression [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%